An overview on the relationship between endometriosis and infertility: the impact on sexuality and psychological well-being. (2nd April 2020) - La Rosa, Valentina Lucia; Barra, Fabio; Chiofalo, Benito; Platania, Alessio; Di Guardo, Federica; Conway, Francesca; Di Angelo Antonio, Silvia; Lin, Li-Te
Abstract: Purpose: Women with endometriosis represent a significant proportion of all outpatient gynecological consultations. Endometriosis is a benign chronic condition characterized by the spreading of endometrial-like tissue outside the uterus. A correlation between endometriosis and infertility has been strongly underlined in the literature about the topic: recent data suggest that up to 50% of women with infertility may suffer from this disease. The aim of this brief commentary is to focus the attention on the importance of a multidisciplinary approach for patients with endometriosis, including an accurate psychological and sexological counselling. Materials and Methods: We propose a brief point of view about a multidisciplinary approach in the treatment of endometriosis and associated infertility. Results and conclusions: Endometriosis is associated to a worse quality of life. Women with endometriosis also report higher levels of psychological conditions such as anxiety and depression. For this reason, an integrative approach is strongly advisable in order to improve social functions and mental health of these women and their partners. This may allow a more correct therapeutic management of these patients, reducing the potential negative impact of the disease on the mental wellbeing of the couple.